Analysis of Food Service Operation Risk Classification and Associated Food Safety Violation Frequency. - Chang, Patrick; Rochani, Haresh; Mase, William A.; Aslan, Asli (Journal of Environmental Health)
Though local health department performance of restaurant inspections plays an important role in preventing foodborne illness, restaurant inspection quality and uniformity often varies across local health department jurisdictions and among employees. In 2012, the Cincinnati Health Department initiated a food safety staff quality improvement initiative. This initiative, part of a Food and Drug Administration national training standards grant initiative, featured standardized training and food safety workforce practices, defined food safety program data collection standards, and refined reporting protocols. The aim of this article was to explore the relationship between the Ohio food safety code violations incurred and the risk classifications to which a Cincinnati food service operation belongs (ranked I-IV based upon potential threat to public safety). A random intercept model was selected to quantify the difference in odds between risk classification categories of incurring violations. Additionally, longitudinal data analysis tracked violation trends across the three years of the study. Main findings were 1) the odds of receiving a food safety violation increased with each year and 2) food establishments categorized as risk class IV had a higher odds of receiving a food safety violation compared with the other risk classifications.